The Perception of Malaysian Rural and Urban Indigenous Women on Body Image - Kui-Ling, Emily Lau; Kiaw, Monna; Hamzah, Nurul Huda; Sercombe, Peter (Melayu: Jurnal Antarabangsa Dunia Melayu, 2021)
This study investigates the perception of body image among indigenous women in Peninsular Malaysia. Using a sample drawn from urban (n=38) and rural (n=21) settings, the study engages participants who are more or less socio-economically acculturated to mainstream society in order to explore different attitudes to body image, and anxiety level about social physique between rural and urban women. Rural indigenous women registered a higher level of body dissatisfaction than their urban counterparts. However, there was no significant difference in attitudes towards body image between indigenous women in both locations. Due to a degree of presumed acculturation to western ideals of body image, urban indigenous women who were not underweight showed a higher anxiety level concerning their physique than those from rural areas with a similar body size. It was also found that a higher level of body dissatisfaction correlated with a poorer body image among indigenous women in Malaysia. Keywords: Body Image, indigenous, Malaysian, perception, rural-urban, women